The effect of teamwork on employee performance in DR Group Holdings / Hasreen Hasmadi - Hasmadi, Hasreen (Faculty of Business and Management, 2019)
This study is to analyzes the effect of teamwork on employee performance in DR Group Holdings which are located in Kota Damansara, Selangor. The questionnaires are distributed to the headquarters employees to gain data. From the data gained, several tools of analysis are used such as descriptive statistical analysis, Pearson correlation analysis and multiple regression analysis. The results show all variables have relationship with employee performance and significant at 0.01 level. Result of multiple regression shown that the variables are significant. Hence, all hypothesis is supported by the regression analysis. The R2 is 0.464 which implies to all the independent variables in this study. As conclusion, the objectives of this study is accepted and it shown that factor abilities is most influential factor that affect employee performance. For recommendations, the researcher suggest that DR Group Holdings need to ensure each team have their own knowledge, skills and abilities. The company also need to plan proper compensation package so that employee able to perform their job well and lastly, the company need to build open communication culture, therefore, the team members can express their ideas, opinions and concern to the teams.